Educational philosophy in the French enlightenment from nature to second nature - Gill, Natasha. (Ashgate, 2010)
Natasha Gill offers the first comprehensive analysis of French educational thought before Rousseau. She situates Emile in the context of a pedagogical debate that had been under way for a century before its publication, reveals the importance of key transitional figures such as Etienne-Gabriel Morelly, and shows how French theorists came to see education as a vehicle through which individual liberation, social harmony and political unity could be achieved.